Photoresist film and its applications

The development of a photoresist film with tailored light absorption properties and thickness range addresses the challenge of forming high-precision patterns, achieving excellent photoresist profiles and enhancing the precision of etching or electroplating processes.

JP7665693B2Active Publication Date: 2025-04-21CHANG CHUN PLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023134361
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-23
Filing Date
2023-08-22
Publication Date
2025-04-21
Estimated Expiration
2043-08-22

AI Technical Summary

Technical Problem

Conventional photoresist films struggle to form highly accurate patterns with a high depth-to-width ratio, leading to low precision in etching or electroplating processes, especially in the printed circuit board industry.

Method used

A photoresist film with specific light absorption properties, characterized by UV-visible spectroscopy, is developed. The film has a thickness range of 60 μm to 600 μm and is absorbed at 405 nm and 436 nm, with absorbance ratios within specific ranges, ensuring excellent photoresist profiles and high precision in etching or electroplating.

Benefits of technology

The photoresist film achieves high-precision etching or electroplating by maintaining a rectangular photoresist pattern shape and minimizing footing length, thereby addressing the limitations of conventional films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665693000001
    Figure 0007665693000001
  • Figure 0007665693000002
    Figure 0007665693000002
  • Figure 0007665693000003
    Figure 0007665693000003
Patent Text Reader

Abstract

To provide a photoresist film and application thereof.SOLUTION: The photoresist film has a thickness T in units of μm. When the photoresist film is characterized by ultraviolet-visible spectroscopy, the photoresist film has absorbance A405nm at 405 nm and absorbance A436nm at 436 nm, where 0<A405nm / T≤0.006 and 0<A436nm / T≤0.005, and the thickness T is 60 μm to 600 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Priority claim This application claims priority to U.S. Provisional Patent Application No. 63 / 374,044, filed on August 31, 2022, and Chinese Patent Application No. 202310582851.0, filed on May 23, 2023. The subject matter of these patent applications is incorporated herein by reference in its entirety.

[0002] FIELD OF THEINVENTION The present application provides a photoresist film, particularly a thick photoresist film, and its applications. [Background technology]

[0003] According to the changes of the photoresist film after exposure and development, photoresist film can be divided into positive photoresist film and negative photoresist film. Positive photoresist film is a type of photoresist in which the part of the photoresist film that is exposed to light dissolves in the photoresist developer, and the part of the photoresist film that is not exposed remains after development. Negative photoresist film is a type of photoresist in which the part of the photoresist film that is not exposed dissolves in the photoresist developer, and the part of the photoresist film that is exposed remains after development.

[0004] In the printed circuit board (PCB) industry, photoresist films are used in etching or electroplating procedures to form circuit patterns. Due to the increasing complexity and size of electronic components, the printed circuit board industry requires thicker photoresist films with higher depth-to-width ratios. However, traditional photoresist films cannot stably form high-precision photoresist patterns after exposure and development, and have poor photoresist profiles or obvious footing, which results in low precision in etching or electroplating. Therefore, an improvement in photoresist films is needed. Summary of the Invention [Means for solving the problem]

[0005] In view of the above technical problems, the present invention provides a photoresist film having an excellent photoresist profile after exposure, which can realize high-precision etching or electroplating processing.

[0006] The object of the present invention is therefore to provide a photoresist film having a thickness T in μm, which, when characterized by UV-Vis spectroscopy, has an absorption A at 405 nm. 405nm , and absorption at 436 nm A 436nm 0 405nm / T≦0.006 and 0 436nm The object of the present invention is to provide a photoresist film having a thickness T of 60 μm to 600 μm, wherein T≦0.005.

[0007] In some embodiments of the present invention, when the photoresist film is characterized by UV-Vis spectroscopy, the photoresist film further has an absorption A of 365 nm. 365nm 0 365nm / T≦0.010.

[0008] ​​​In some embodiments of the present invention, UV-Vis spectroscopy is measured using a UV-Vis spectrophotometer under the following operating conditions: The photoresist film is arranged perpendicular to the direction of the incident light, the diffraction grating is configured as a light splitter, the test temperature is 25°C, the test pressure is 1 atm, the analysis mode is absorbance, the scanning wavelength range is 190nm-1100nm, the blank sample is air, the scanning speed is 2200nm / min, the light source is switched from a deuterium lamp to a tungsten lamp, the switch wavelength is 340.8nm, the sampling interval is 0.2nm, and the slit width is 2.0nm.

[0009] In some embodiments of the present invention, the photoresist film is a negative photoresist film.

[0010] In some embodiments of the present invention, 0 405nm / T≦0.002 and 0 436nm / T≦0.001.

[0011] In some embodiments of the present invention, the photoresist film comprises (A) an alkali-soluble polymer, (B) an ethylenically unsaturated compound component, and (C) a photopolymerization initiator.

[0012] In some embodiments of the present invention, the ethylenically unsaturated compound component is a difunctional acrylic compound.

[0013] Based on the weight of the ethylenically unsaturated compound component, the amount of the difunctional acrylic compound can be 60% by weight or more.

[0014] Another object of the present invention is to provide a composite film, comprising the above-mentioned photoresist film and a protective film on at least one surface of the photoresist film.

[0015] ​​The protective film may be selected from the group consisting of polyethylene terephthalate films, polyolefin films, and composites thereof.

[0016] In order to make the above objects, technical features and advantages of the present invention more apparent, the present invention will be described in detail below with reference to some specific embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Some specific embodiments of the present invention will now be described in detail, however, the present invention may be embodied in various embodiments and should not be limited to the embodiments set forth herein.

[0018] Unless otherwise specifically stated, the terms "a," "the," "the" and the like used in the specification and claims are intended to include both the singular and the plural forms.

[0019] Unless otherwise specified, the terms "first", "second", etc. in the present specification and claims have no special meaning and are used only to distinguish between the elements or components described. These terms are not used to indicate priority.

[0020] Unless otherwise specified, the terms "(meth)acrylic acid", "(meth)acrylate", and the like described in the present specification and claims are intended to cover both embodiments in which the functional group in the parentheses is included and those in which it is not included. For example, the term "carboxy-containing (meth)acrylic acid-based polymer" is intended to cover both carboxy-containing acrylic acid-based polymers and carboxy-containing methacrylic acid-based polymers. The term "methyl (meth)acrylate" is intended to cover both methyl acrylate and methyl methacrylate.

[0021] In this specification and claims, weight average molecular weight (Mw) is measured by gel permeation chromatography (GPC) and calculated by comparison with a standard sample. The unit of weight average molecular weight (Mw) is "g / mol".

[0022] The advantages of the present invention over the prior art are mainly: 405nm / T and A 436nm The aim is to provide a photoresist film having an excellent photoresist profile after exposure by controlling / T within a specific range, thereby realizing highly accurate etching or electroplating processing. The photoresist film and its application are described in detail below.

[0023] 1. Photoresist film A photoresist film as described herein refers to a film that includes a photosensitive resin composition.

[0024] In order to facilitate storage of the photoresist film and prevent contamination or damage by foreign substances, a protective film can be additionally provided on the surface of the photoresist film to provide a function of protection and support. Unless otherwise described, the terms "thickness" and "absorbance" described in this specification and claims refer to the photoresist film itself and do not include other parts such as protective films combined with the photoresist film. Photoresist films are further described below.

[0025] 1.1.Characteristics of photoresist film The photoresist film of the present invention has specific light absorption characteristics. In particular, when the photoresist film is characterized by UV-Vis spectroscopy, the photoresist film has an absorption A of 405 nm. 405nm , and absorption at 436 nm A 436nm and absorbance A 405nm and the thickness T of the photoresist film (unit: μm), 405nm / T≦0.006, and the absorbance A 436nm and the thickness T of the photoresist film, <A​436nm / T≦0.005. For example, A 405nm / T can be 0.0005, 0.001, 0.0015, 0.002, 0.0025, 0.003, 0.0035, 0.004, 0.0045, 0.005, 0.0055, or 0.006, or within a range between any two of these listed values. 436nm / T can be 0.0005, 0.001, 0.0015, 0.002, 0.0025, 0.003, 0.0035, 0.004, 0.0045, or 0.005, or within a range between any two of these listed values. 405nm / T or A 436nm If / T is not within the above range, the photoresist pattern formed by the photoresist film after exposure and development is not suitable for etching or electroplating processing, which requires high precision. 405nm / T≦0.002 and 0 436nm / T≦0.001.

[0026] In some embodiments of the present invention, when the photoresist film is characterized by UV-Vis spectroscopy, the photoresist film further has an absorption A of 365 nm. 365nm 0 365nm / T≦0.010, and the unit of T is μm. For example, A 365nm / T can be 0.0005, 0.001, 0.0015, 0.002, 0.0025, 0.003, 0.0035, 0.004, 0.0045, 0.005, 0.0055, 0.006, 0.0065, 0.007, 0.0075, 0.008, 0.0085, 0.009, 0.0095 or 0.010, or within a range between any two of these listed values.

[0027] ​​​In the present invention, the UV-Vis spectroscopy is measured by using a UV-Vis spectrophotometer under the following operating conditions, the photoresist film is arranged perpendicular to the direction of the incident light, the diffraction grating is configured as a light splitter, the test temperature is 25°C, the test pressure is 1 atm, the analysis mode is absorbance, the scanning wavelength range is 190nm-1100nm, the blank sample is air, the scanning speed is 2200nm / min, the switch wavelength for switching the light source from a deuterium lamp to a tungsten lamp is 340.8nm, the sampling interval is 0.2nm, and the slit width is 2.0nm. Under the above operating conditions, the composite film including the photoresist film and the protective film on the two sides of the photoresist film is cut into a size of 5cm x 3cm along the transverse direction (TD) and the flow direction (MD) at an arbitrary position, and the protective film is peeled off from the cut photoresist film to obtain a photoresist film sample. The photoresist film must be arranged perpendicular to the direction of the incident light, so that the absorbance of the photoresist film can be measured correctly. The tungsten lamp used as the incident light source has a wavelength range greater than 340.8 nm. Also, the "sampling interval" means that data is collected and recorded every 0.2 nm within the scanning wavelength range of 190 nm to 1100 nm.

[0028] Absorbance A of the photoresist film of the present invention 405nm , A 436nm and A 365nm The value of can be adjusted by adjusting the composition of the photoresist film and the drying conditions of the preparation process of the photoresist film. For example, the composition of the photoresist film can be adjusted by selecting the type and amount of additives. Examples of additives include, but are not limited to, photoinitiators, light absorbers, dyes, etc. Those skilled in the art can achieve the desired absorbance using conventional experimentation based on the description of the present application.

[0029] The thickness T of the photoresist film of the present invention is expressed in μm. The thickness T is in the range of 60 μm to 600 μm, preferably in the range of 100 μm to 600 μm. For example, the thickness T is 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm, 450 μm, 460 μm, 470 μm, 480 μm, 490 μm, 500 μm, 510 μm, 520 μm, 530 μm, 540 μm, 550 μm, 560 μm, 570 μm, 580 μm, 590 μm, 60 ... The thickness of the photoresist film can be 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm, 450 μm, 460 μm, 470 μm, 480 μm, 490 μm, 500 μm, 510 μm, 520 μm, 530 μm, 540 μm, 550 μm, 560 μm, 570 μm, 580 μm, 590 μm, or 600 μm, or within the range between these two values. The thicker the photoresist film, the thicker the possible thickness of the metal conductive layer. Therefore, the photoresist film of the present invention is particularly suitable for the packaging of 2.5D and 3D integrated circuits, and is useful for patterning before plating of the conductive layer.

[0030] The photoresist film of the present invention can be a positive photoresist film or a negative photoresist film. In some embodiments of the present invention, the photoresist film of the present invention is a negative photoresist film. After exposure, the unexposed portions of the photoresist film dissolve in a photoresist developer, and after development, the exposed portions of the photoresist film remain.

[0031] In an embodiment of the present invention, the photoresist film of the present invention is a dry film, i.e., a resin film with a low solvent content. The low solvent content is 10% by weight or less, particularly 5% by weight or less, more particularly 0.1-4% by weight, based on the total weight of the photoresist film. In contrast to ink-like and liquid-like wet films, dry films are less likely to flow or deform due to their low solvent content, and can be attached to a substrate without the need for additional processes such as coating or drying. Therefore, dry films are easy to control and have excellent operability.

[0032] 1.2. Photoresist film components 0 405nm / T≦0.006 and 0 436nm Provided that / T≦0.005, the components of the photoresist film of the present invention can be adjusted as necessary. In some embodiments of the present invention, the photoresist film is a negative photoresist film. The photoresist film includes (A) an alkali-soluble polymer, (B) an ethylenically unsaturated compound component, and (C) a photopolymerization initiator, and can further include additives as needed.

[0033] 1.2.1.(A) Alkali-soluble polymer The alkali-soluble polymer is a carboxy-containing polymer. Examples of the alkali-soluble polymer include, but are not limited to, carboxy-containing acrylic acid-based polymer, carboxy-containing vinyl aromatic-based polymer, carboxy-containing norbornene-based polymer, carboxy-containing epoxy-based polymer, carboxy-containing amide-based polymer, carboxy-containing amide epoxy-based polymer, carboxy-containing alkyd-based polymer, and carboxy-containing phenol-based polymer. The above alkali-soluble polymer can be used alone or in combination. In some embodiments of the present invention, the alkali-soluble polymer is a carboxy-containing acrylic acid-based polymer.

[0034] ​​An alkali-soluble polymer can be obtained by polymerizing one or more carboxy-containing polymerizable monomers, or by copolymerizing one or more carboxy-containing polymerizable monomers with other polymerizable monomers that do not contain carboxyl. Thus, the alkali-soluble polymer can contain one or more repeat units derived from the carboxy-containing polymerizable monomer, or one or more repeat units derived from the carboxy-containing polymerizable monomer and one or more repeat units derived from the other polymerizable monomer.

[0035] In some embodiments of the present invention, the alkali-soluble polymer has at least one repeat unit derived from a first polymerizable monomer and at least one repeat unit derived from a second polymerizable monomer, and the first polymerizable polymer contains carboxy. Examples of the first polymerizable monomer include, but are not limited to, (meth)acrylic acid, β-bromo(meth)acrylic acid, α-chloro(meth)acrylic acid, β-phthalimido(meth)acrylic acid, β-styryl(meth)acrylic acid, propiolic acid, fumaric acid, cinnamic acid, crotonic acid, itaconic acid, and maleic acid. The second polymerizable monomer does not contain carboxy. Examples of the second polymerizable monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tert-butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 1-methylcyclopentyl (meth)acrylate, 1-methylcyclohexyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, 2-butyl-2-adamantyl (meth)acrylate, tetrahydrofur ... (meth)acrylate-based compounds such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, glycidyl methacrylate, 2,2,2-trifluoroethyl (meth)acrylate, and 2,2,3,3-tetrafluoropropyl (meth)acrylate; (meth)acrylonitrile; vinyl ester-based compounds such as vinyl acetate and vinyl n-butylate; vinyl aromatic compounds such as styrene, vinyl naphthalene, 3-acetoxystyrene, 4-acetoxystyrene, vinyl toluene, and α-methylstyrene; norbornene; acrylamide; maleate-based compounds such as monomethyl maleate, monoethyl maleate, and monoisopropyl maleate; and derivatives of the above polymerizable monomers, but are not limited to these.The first polymerizable monomer and the second polymerizable monomer may be used alone or in combination.

[0036] In a preferred embodiment of the present invention, an alkali-soluble polymer can be obtained by copolymerizing (meth)acrylic acid with one or more (meth)acrylate compounds. Thus, the alkali-soluble polymer can contain repeating units derived from (meth)acrylic acid and repeating units derived from (meth)acrylate compounds. The weight ratio of (meth)acrylic acid to (meth)acrylate compounds can be 1:20 to 1:1, more particularly 1:6 to 1:4. For example, the weight ratio of (meth)acrylic acid to (meth)acrylate compounds can be 1:20, 1:19, 1:18, 1:17, 1:16, 1:15, 1:14, 1:13, 1:12, 1:11, 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, or 1:1, or within a range between any two of these listed values.

[0037] The average molecular weight of the alkyl-soluble polymer can be 10,000 to 180,000, preferably 40,000 to 80,000. For example, the weight average molecular weight of the alkyl-soluble polymer can be 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, 55,000, 60,000, 65,000, 70,000, 75,000, 80,000, 85,000, 90,000, 95,000, 10 ... In one embodiment, the amount of the at least one ion exchange rate can be 0.05,000, 110,000, 115,000, 120,000, 125,000, 130,000, 135,000, 140,000, 145,000, 150,000, 155,000, 160,000, 165,000, 170,000, 175,000, or 180,000, or within a range between any two of these recited values.

[0038] Based on the total weight of the photoresist film, the amount of alkyl-soluble polymer can be 20% to 85% by weight, particularly 40% to 80% by weight, more particularly 50% to 75% by weight. For example, based on the total weight of the photoresist film, the amount of alkyl-soluble polymer can be 20% by weight, 22.5% by weight, 25% by weight, 27.5% by weight, 30% by weight, 32.5% by weight, 35% by weight, 37.5% by weight, 40% by weight, 42.5% by weight, 45% by weight, 47.5% by weight, 50% by weight, 52.5% by weight, 55% by weight, 57.5% by weight, 60% by weight, 62.5% by weight, 65% by weight, 67.5% by weight, 70% by weight, 72.5% by weight, 75% by weight, 77.5% by weight, 80% by weight, 82.5% by weight, or 85% by weight, or within a range between two of these recited values.

[0039] 1.2.2.(B) Ethylenically unsaturated compound components The ethylenically unsaturated compound refers to a compound having at least one reactive ethylenic functional group, preferably a difunctional compound having two reactive ethylenic functional groups. In some embodiments of the present invention, the ethylenically unsaturated compound component includes a monofunctional or polyfunctional acrylic acid compound, preferably a difunctional acrylic acid compound. Examples of acrylic acid-based compounds include, but are not limited to, ethoxylated trimethylolpropane triacrylate, ethoxylated bisphenol-A diacrylate, ethoxylated bisphenol-A dimethacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, polypropylene glycol diacrylate, tris((meth)acryloxyisocyanate)hexamethylene isocyanurate, ethoxylated urethane di(meth)acrylate, propoxylated urethane di(meth)acrylate, ethoxylated / propoxylated urethane di(meth)acrylate, ethoxylated tris(methacryloxyisocyanate)hexamethylene isocyanurate, acrylated tris(methacryloxyisocyanate)hexamethylene isocyanurate, ethoxylated / propoxylated tris(methacryloxyisocyanate)hexamethylene isocyanurate. Based on the weight of the ethylenically unsaturated compound component, the amount of the difunctional acrylic acid compound is preferably 60% by weight or more.For example, based on the weight of the ethylenically unsaturated compound component, the amount of the difunctional acrylic acid compound can be 60% by weight, 62.5% by weight, 65% by weight, 67.5% by weight, 70% by weight, 72.5% by weight, 75% by weight, 77.5% by weight, 80% by weight, 82.5% by weight, 85% by weight, 87.5% by weight, 90% by weight, 92.5% by weight, 95% by weight, 97.5% by weight, or 100% by weight, or within the range between these two values.

[0040] In some embodiments of the present invention, the ethylenically unsaturated compound component includes ethoxylated trimethylolpropane triacrylate and ethoxylated bisphenol-A dimethacrylate.

[0041] Based on the total weight of the photoresist film, the amount of the ethylenically unsaturated compound component can be 5% by weight to 70% by weight, particularly 15% by weight to 50% by weight, more particularly 20% by weight to 45% by weight. For example, based on the total weight of the photoresist film, the amount of the ethylenically unsaturated compound component can be 5% by weight, 7.5% by weight, 10% by weight, 12.5% ​​by weight, 15% by weight, 17.5% by weight, 20% by weight, 22.5% by weight, 25% by weight, 27.5% by weight, 30% by weight, 32.5% by weight, 35% by weight, 37.5% by weight, 40% by weight, 42.5% by weight, 45% by weight, 47.5% by weight, 50% by weight, 52.5% by weight, 55% by weight, 57.5% by weight, 60% by weight, 62.5% by weight, 65% by weight, 67.5% by weight, or 70% by weight, or within a range between two of these listed values.

[0042] 1.2.3.(C) Photoinitiator A photopolymerization initiator refers to a substance that can initiate a polymerization reaction in the presence of light. The type of photopolymerization initiator is not particularly limited. Examples of photopolymerization initiators include, but are not limited to, imidazole-based compounds, ketone-based compounds, quinone-based compounds, benzoin-based or benzoin ether-based compounds, polyhalogenated compounds, triazine-based compounds, organic peroxide compounds, onium compounds, and other commonly known photopolymerization initiators. The photopolymerization initiators can be used alone or in combination.

[0043] Examples of imidazole compounds include, but are not limited to, 2,4,5-triarylimidazole dimers such as 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, and 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer.

[0044] Examples of ketone compounds include, but are not limited to, benzophenone, 4,4-bis(dimethylamino)benzophenone, 4-methoxy-4'-dimethylaminobenzophenone, 4,4'-dimethoxybenzophenone, 4-dimethylaminobenzophenone, 4-dimethylaminoacetophenone, xanthone, thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, acridone, α-hydroxyacetophenone, α-aminoacetophenone, α-hydroxycycloalkylphenone, and dialkylacetophenone.

[0045] Examples of quinone compounds include, but are not limited to, camphorquinone, benzanthraquinone, 2-tert-butylanthraquinone, and 2-methylanthraquinone.

[0046] Examples of benzoin or benzoin ether compounds include, but are not limited to, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, and benzoin phenyl ether.

[0047] Examples of polyhalogenated compounds include, but are not limited to, carbon tetrabromide, phenyl tribromomethyl sulfone, and phenyl trichloromethyl ketone.

[0048] Examples of triazine compounds include, but are not limited to, 2,4,6-tris(trichloromethyl)-s-triazine, 2-methoxy-4,6-bis(trichloromethyl)-s-triazine, 2-amino-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-methoxyphenylethynyl)-4,6-bis(trichloromethyl)-s-triazine.

[0049] Examples of organic peroxide compounds include, but are not limited to, methyl ethyl ketone peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, benzoyl peroxide, di-tert-butyl isophthalate peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butyl peroxybenzoate, a,a'-bis(tert-butylperoxyisopropyl)benzene, dicumyl peroxide, and 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone.

[0050] Examples of onium compounds include, but are not limited to, diaryliodonium or triarylsulfonium salts obtained by combining diphenyliodonium, 4,4'-dichlorodiphenyliodonium, 4,4'-dimethoxydiphenyliodonium, 4,4'-di-tert-butyldiphenyliodonium, 4-methyl-4'-isopropyldiphenyliodonium, or 3,3'-nitrodiphenyliodonium with chloride, bromide, tetrafluoroborate, hexafluorophosphate, hexafluoroarsenate, hexafluoroantimonate, tetrakis(pentafluorophenyl)borate, or trifluoromethanesulfonic acid.

[0051] Other common well-known examples of photoinitiators include, but are not limited to, fluorine, bisacylphosphine oxides, azinium compounds, organoboron compounds, phenylglyoxylates, and titanocenes.

[0052] In some embodiments of the present invention, the photoinitiator is an imidazole-based compound or a ketone-based compound.

[0053] In the photoresist film of the present invention, the amount of photopolymerization initiator can be 0.1 wt % to 15 wt %, specifically 0.5 wt % to 10 wt %, and more specifically 1 wt % to 5 wt %, based on the total weight of the photoresist film. For example, based on the total weight of the photoresist film, the amount of photoinitiator can be 0.1 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 12.5 wt%, 13 wt%, 13.5 wt%, 14 wt%, 14.5 wt%, or 15 wt%, or within a range between any two of these recited values.

[0054] 1.2.4. Optional Additives 0 405nm / T≦0.006 and 0 436nm Provided that / T≦0.005, the photoresist film of the present invention can further comprise additives to improve the properties of the photoresist film. Examples of the additives include, but are not limited to, light absorbers, dyes, pigments, radical initiators, and surfactants. The additives can be used alone or in combination. In some embodiments of the present invention, the photoresist film further comprises a light absorber to adjust the absorption of the photoresist film at a specific wavelength.

[0055] 1.3. Preparation of photoresist film ​​The method for preparing the photoresist film of the present invention is not particularly limited. Those skilled in the art can prepare the photoresist film of the present invention based on the description of the specification of the present application. For example, when preparing the negative photoresist film, the photoresist film can be prepared by the following steps: (A) mixing each component of the photoresist film including an alkali-soluble polymer, (B) an ethylenically unsaturated compound, (C) a photopolymerization initiator, and other optional additives uniformly with a stirrer, and dissolving or dispersing these components in a solvent to provide a resin composition; coating the resin composition on a circuit board; and drying the coated resin composition to obtain a photoresist film. The detailed preparation method will be described in the following examples.

[0056] 2. Applying photoresist film Generally, in order to facilitate the storage of the photoresist film and prevent damage and contamination by foreign substances, each surface of the photoresist film is covered with a protective film to provide protection and support before use.Therefore, the present invention also provides a composite film comprising the above-mentioned photoresist film and a protective film on at least one surface of the photoresist film.In a preferred embodiment of the present invention, a protective film is provided on each surface of the photoresist film, and the materials of the protective films on different surfaces of the photoresist film can be the same or different.

[0057] The type of protective film is not particularly limited and can be any conventional film known in the art. For example, the protective film can be selected from the group consisting of polyethylene terephthalate film (PET film), polyolefin film, and their composites. Examples of polyolefin films include, but are not limited to, polyethylene film (PE film) and polypropylene film (PP film), such as polypropylene stretched film. The composite can be a composite of polyethylene terephthalate film and polyolefin film, or a composite of different polyolefin films. In a preferred embodiment of the present invention, the composite film includes a PET film on one surface of the photoresist film and a PE film on the other surface of the photoresist film.

[0058] The method for preparing the composite film of the present invention is not particularly limited and can be any method known in the art. A person skilled in the art can prepare the composite film based on the description of the present specification. For example, the composite film can be prepared by stacking protective films on both surfaces of a photoresist film to provide a laminate, and pressing the laminate to obtain a composite film. Alternatively, the composite film can be prepared by coating a resin composition for forming a photoresist film on a first protective film, drying the coated resin composition to form a photoresist film on the first protective film, and then adhering a second protective film on the surface of the photoresist film that is not in contact with the first protective film. Alternatively, the composite film can be prepared by extruding a resin composition for forming a photoresist film into a gap between two protective films kept at a predetermined distance, and then drying the extruded resin composition to form a photoresist film between the two protective films. EXAMPLES

[0059] 3. Working Example Test Method [Photoresist film thickness] The prepared composite film containing the photoresist film was cut into a size of 5 cm x 3 cm. Then, the protective films on both surfaces of the photoresist film were peeled off. The obtained photoresist film was placed on the platform (MS-11C platform) of a film thickness gauge (Model: Nikon Digimicro MFC-101+MS-11C, manufactured by Nikon Corporation) and measured using the MFC-101 counter at a test pressure of 140 gf. The thickness of the photoresist film was determined by measuring 10 different points and averaging the measured values.

[0060] [Photoresist film absorbance] The prepared composite film containing the photoresist film was cut into a size of 5 cm × 3 cm. Then, the protective films on both surfaces of the photoresist film were peeled off. The obtained photoresist film was measured by using an ultraviolet-visible spectrophotometer (model: Shimadzu UV-1601, manufactured by Shimadzu Corporation) in the following manner. The photoresist film was positioned perpendicular to the direction of the incident light using a jig. The measurement was carried out under the following operating conditions. The diffraction grating was configured as a light splitter, the test temperature was 25 °C, the test pressure was 1 atm, the analysis mode was absorbance, the scanning wavelength range was 190 nm to 1100 nm, the blank sample was air, the scanning speed was 2200 nm / min, the light source was switched from a deuterium lamp to a tungsten lamp, the switch wavelength was 340.8 nm, the sampling interval was 0.2 nm, the slit width was 2.0 nm, and for analysis, the Shimadzu UV Probe V1.11 software was used. The absorption A at 405 nm was 1.0 nm. 405nm , absorption at 436 nm A 436nm , and absorption at 365 nm A 365nm obtained.

[0061] [Photoresist pattern fragment shape] A Ti(600A) / Cu(2000A) wafer with a diameter of 6 inches and a thickness of 625 μm was preheated at 80°C for 10 minutes in a batch oven, and the temperature of the surface of the wafer was maintained at 50°C before pressing the film. A photoresist film was placed on the surface of the wafer and pressed using a film laminator (model: CSL-M25E, manufactured by C SUN Co., Ltd.). The pressing temperature was 105°C and the pressing pressure was 3 kg / cm. 2 and the pressing speed was 2.0 m / min. After pressing was completed, the excess of the film was removed and the resulting photoresist film sample was allowed to cool to room temperature for 15 minutes.

[0062] The minimum development time is the following steps: prepare a 0.9% to 1.1% Na2CO3 aqueous solution, set the temperature of the aqueous solution to 29°C to 31°C, and set the spray pressure to 2.0 kg / cm 2 The photoresist film sample was placed in a developing machine (model: S30C, manufactured by Pioneer Technology Engineering Co., Ltd.) together with a wafer, and "flash" and "swing" were operated. Here, the length of the developing section was 1.3 m, and the length of the cleaning section was 1.3 m. The time when the photoresist was completely developed and removed was recorded as the minimum development time (MDT).

[0063] The photoresist film was exposed using a stepper (model: Ultratech Stepper Spectrum, manufactured by Ultratech). The wavelengths of the exposure light sources were 405 nm, 436 nm, and 365 nm, respectively. The exposure energy was 800 mJ / cm 2 The exposure process was continued until the photoresist pattern had a depth to width ratio of 2.0 and a patterned to non-patterned ratio (i.e., via diameter:photoresist width) of 1:1. After the exposure was completed, the exposed photoresist film was left for 30 minutes. Then, a 0.9% to 1.1% Na2CO3 aqueous solution was used, the solution temperature was set to 29°C to 31°C, and the spray pressure was set to 2.0 kg / cm. 2and the developing time was set to twice the minimum developing time (MDT×2) to develop the exposed photoresist film, thereby obtaining a developed photoresist film.

[0064] The developed photoresist film together with the wafer was cut at the non-patterned portion (via portion) with a wafer cutter, and the cross-sectional shape of the photoresist pattern was observed using a scanning electron microscope. Here, the specimen was tilted 75° and the magnification was 200 times. The cross-section of the photoresist was randomly selected, and the width of the photoresist was measured at the positions of 1 / 25, 2 / 25, 3 / 25, 4 / 25 and 5 / 25 of the total thickness of the photoresist calculated from the top end of the photoresist (the end away from the wafer), and the top width was obtained by averaging the five measured values. In addition, the width of the photoresist was measured at the positions of 1 / 25, 2 / 25, 3 / 25, 4 / 25 and 5 / 25 of the total thickness of the photoresist calculated from the bottom end of the photoresist (the end in contact with the wafer), and the bottom width was obtained by averaging the five measured values. If the value of "|(top width-bottom width)| / thickness" is less than 0.04, the result was recorded as "rectangle", which means that the cross-sectional shape of the photoresist pattern is good. If the value of "|(top width-bottom width)| / thickness" is 0.04 or more, the result is recorded as "trapezoidal", which means the cross-sectional shape of the photoresist pattern is poor. In the formula, "|(top width-bottom width)|" represents the absolute value of "(top width-bottom width)".

[0065] [Length of the footing of the photoresist pattern] A Ti(600A) / Cu(2000A) wafer with a diameter of 6 inches and a thickness of 625 μm was preheated at 80°C for 10 minutes in a batch oven, and the temperature of the surface of the wafer was maintained at 50°C before pressing the film. A photoresist film was placed on the surface of the wafer and pressed using a film laminator (model: CSL-M25E, manufactured by C SUN Co., Ltd.). The pressing temperature was 105°C and the pressing pressure was 3 kg / cm. 2and the pressing speed was 2.0 m / min. After pressing was completed, the excess of the film was removed and the resulting photoresist film sample was allowed to cool to room temperature for 15 minutes.

[0066] The photoresist film was exposed using a stepper (model: Ultratech Stepper Spectrum, manufactured by Ultratech). The wavelengths of the exposure light sources were 405 nm, 436 nm, and 365 nm, respectively. The exposure energy was 800 mJ / cm 2 The exposure process was continued until the desired photoresist pattern had a depth to width ratio of 2.0 and a patterned to non-patterned ratio (i.e., via diameter:photoresist width) of 1:1. After the exposure was completed, the exposed photoresist film was left for 30 minutes to 24 hours. Then, a 0.9% to 1.1% Na2CO3 aqueous solution was used, the solution temperature was set to 29°C to 31°C, and the spray pressure was set to 2.0 kg / cm. 2 The exposure time was set to 2 times the minimum development time (MDT x 2) and 4 times the minimum development time (MDT x 4), and the exposed photoresist film was developed, thereby obtaining a developed photoresist film. The minimum development time (MDT) was based on the test result of the minimum development time described in the section [Cross-sectional shape of photoresist pattern].

[0067] The developed photoresist film together with the wafer was cut by a wafer cutter at the non-patterned portion (via portion), and the cross-sectional shape of the photoresist pattern was observed using a scanning electron microscope. Here, the specimen was tilted 75° and the magnification was 5000 times. The cross section of the photoresist was randomly selected, and the side where the bottom of the photoresist protruded more toward the non-photoresist pattern portion was selected to measure the footing length. The footing length was measured as follows. The position of the photoresist sidewall, which was 1 / 5 of the total thickness of the photoresist from the bottom end of the photoresist, was used as the reference point, and a reference line was drawn that extended downward from the reference point and was perpendicular to the surface of the wafer. The distance between the "intersection of the reference line and the surface of the wafer" and the "intersection of the sidewall of the photoresist and the surface of the wafer", i.e., the footing length, was calculated.

[0068] 3.2. Preparation and testing of photoresist films 3.2.1. Synthesis of alkali-soluble polymers According to the following synthesis examples 1 to 3, carboxy-containing acrylic acid polymers were prepared as alkali-soluble polymers.

[0069] [Synthesis Example 1] As copolymerization monomers, 15 g of methacrylic acid, 50 g of methyl methacrylate, 30 g of butyl acrylate, and 5 g of butyl methacrylate were mixed with 1.0 g of azobisisoheptylnitrile to prepare solution a1. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in 20 g of ethyl acetate to prepare solution b1.

[0070] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and 80 g of ethyl acetate (solvent) was added to the flask and heated to 70 ° C. Solution a1 was added dropwise to the flask at a constant rate over 3 hours, and the solution in the flask was maintained at a temperature of 70 ° C and stirred for 2 hours. Solution b1 was added dropwise to the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70 ° C and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90 ° C and stirred for 5 hours to fully carry out the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer A (hereinafter referred to as polymer A) having a weight average molecular weight of 65,000 and a solid content of 50 wt%.

[0071] [Synthesis Example 2] As copolymerization monomers, 15 g of methacrylic acid, 65 g of methyl methacrylate, 10 g of butyl acrylate, and 10 g of butyl methacrylate were mixed with 0.75 g of azobisisoheptylnitrile to prepare solution a2. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in 20 g of ethyl acetate to prepare solution b2.

[0072] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and 102.2 g of ethyl acetate was added to the flask and heated to 70 ° C. Solution a2 was added dropwise to the flask at a constant rate over 3 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 2 hours. Solution b2 was added dropwise to the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70 ° C. and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90 ° C. and stirred for 5 hours to fully carry out the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer B (hereinafter referred to as polymer B) having a weight average molecular weight of 65,000 and a solid content of 45 wt%.

[0073] [Synthesis Example 3] As copolymerization monomers, 20 g of methacrylic acid, 45 g of methyl methacrylate, and 35 g of 2-ethylhexyl acrylate were mixed with 0.5 g of azobisisoheptylnitrile to prepare solution a3. Separately, 0.5 g of azobisisoheptylnitrile was dissolved in 20 g of ethyl acetate to prepare solution b3.

[0074] A flask equipped with a stirrer, reflux condenser, thermometer and pipette was prepared, and 80g of ethyl acetate was added to the flask and heated to 70°C. Solution a3 was added dropwise to the flask at a constant rate over 3 hours, and the solution in the flask was maintained at a temperature of 70°C and stirred for 2 hours. Solution b3 was added dropwise to the flask at a constant rate over 0.5 hours, and the solution in the flask was maintained at a temperature of 70°C and stirred for 5 hours. Thereafter, the solution in the flask was heated to 90°C and stirred for 5 hours to fully carry out the reaction. After the reaction was completed, the resultant was cooled to room temperature to obtain a carboxy-containing acrylic acid-based polymer C (hereinafter referred to as polymer C) having a weight average molecular weight of 55,000 and a solid content of 50% by weight.

[0075] 3.2.2. Preparation of photoresist film Information regarding the raw materials used in the following Examples and Comparative Examples is shown in Table 1 below.

[0076] [Table 1]

[0077] The components were mixed according to the ratios shown in Table 2 and stirred for 1 hour to obtain a resin composition. The obtained resin composition was coated onto a PET film functioning as a protective film using a Kodaira wire-wound rod. The coated resin composition was dried in an oven at 100°C for 24 hours. The surface of the dried resin composition was then covered with a PE film functioning as a protective film. Thereby, photoresist films (i.e., composite films) covered with protective films of Examples 1 to 7 (E1 to E7) and Comparative Examples 1 to 5 (CE1 to CE5) were obtained.

[0078] [Table 2]

[0079] 3.2.3. Photoresist film testing According to the above-mentioned test methods, the photoresist films of Examples 1 to 7 and Comparative Examples 1 to 5 were tested. The results are shown in Table 3.

[0080] [Table 3]

[0081] As shown in Table 3, the photoresist films of Examples 1 to 7 (E1 to E7) of the present invention had a 0 405nm / T≦0.006 and 0 436nm The photoresist pattern formed after exposure and development of the photoresist film has a rectangular shape and a short footing length (less than 10 μm). This means that the photoresist pattern has a good photoresist profile, respectively. In particular, Examples 3 and 7 (E3 and E7) show that the photoresist film is 0. 405nm / T≦0.002 and 0 436nm It is further shown that when the photoresist pattern has the characteristic of / T≦0.001, it has the shortest footing length and therefore the best photoresist profile. In contrast, the photoresist films of Comparative Examples 1 to 5 (CE1 to CE5) have a 0 405nm / T≦0.006 and 0 436nm The photoresist pattern formed after exposure and development of the comparative photoresist film does not have the feature of / T≦0.005, and does not have a rectangular shape, and has a longer footing length. This means that the photoresist pattern has a poor photoresist profile. Such a photoresist film is not useful for etching or electroplating processing that requires high precision.

[0082] ​​​​​​ The above embodiments explain the principles and effects of the present invention and demonstrate its inventive features. Those skilled in the art can make various modifications and replacements based on the disclosure and suggestions of the invention described. Therefore, the protection scope of the present invention is defined in the appended claims.

Claims

1. A photoresist film for an exposure light source including light having wavelengths of 405 nm, 436 nm, and 365 nm, the photoresist film has a thickness T in μm; When the photoresist film is characterized by UV-Vis spectroscopy, the photoresist film has an absorption A of 405 nm. 405nm , Absorption A at 436 nm 436nm , and absorption at 365 nm A 365nm and 0<A 405nm / T ≦ 0.006, 0 < A 436nm / T ≦ 0.004, and 0 < A 365nm / T≦0.010, and the thickness T is 60 μm to 600 μm; UV-Vis spectroscopy was measured using a UV-Vis spectrophotometer under the following operating conditions: The photoresist film is arranged perpendicular to the direction of the incident light, the diffraction grating is configured as a light splitter, the test temperature is 25° C., the test pressure is 1 atmosphere, the analysis mode is absorbance, the scanning wavelength range is 190 nm to 1100 nm, the blank sample is air, the scanning speed is 2200 nm / min, the switch wavelength for switching the light source from a deuterium lamp to a tungsten lamp is 340.8 nm, the sampling interval is 0.2 nm, and the slit width is 2.0 nm.

2. 10. The photoresist film of claim 1 which is a negative photoresist film.

3. 0<A 405nm / T ≦ 0.002, and 0 < A 436nm 2. The photoresist film of claim 1 , wherein / T≦0.

001.

4. (A) an alkali-soluble polymer, (B) an ethylenically unsaturated compound component, and 2. The photoresist film of claim 1, further comprising (C) a photopolymerization initiator.

5. 5. The photoresist film of claim 4, wherein the ethylenically unsaturated compound component is a difunctional acrylic acid compound.

6. 6. The photoresist film of claim 5, wherein the amount of the difunctional acrylic acid compound is 60% by weight or more, based on the weight of the ethylenically unsaturated compound component.

7. The photoresist film according to any one of claims 1 to 6, and A composite film including a protective film on at least one surface of the photoresist film.

8. 8. The composite film of claim 7, wherein the protective film is selected from the group consisting of polyethylene terephthalate films, polyolefin films, and composites thereof.

Citation Information

Patent Citations

  • Curable composition

    JP2022122265A

  • Photosensitive resin multilayer body

    WO2022085366A1